Characterization of HMW glutenin subunit Bx7OE and its distribution in common wheat and related species. Issue 2 (August 2014) - Li, Jie; Han, Caixia; Zhen, Shoumin; Li, Xiaohui; Yan, Yueming
<x content-type="archive" xml:space="preserve">Abstract</x> The overexpression of wheat Bx7 subunit (Bx7OE) encoded by the Glu-B1al allele is originated from a duplication event of the Bx7 gene, and has a positive effect on gluten strength. Thus, it is an important genetic resource for wheat quality improvement. In this study, the Bx7OE subunit from a large number of bread wheat and related species was characterized by sodium dodecyl sulphate–polyacrylamide gel electrophoresis, reversed-phase high-performance liquid chromatography (RP-HPLC) and Sequence-Tagged sites (STS) markers. Only 31 bread wheat varieties were found to carry Bx7OE. RP-HPLC quantification analysis revealed that the mean proportion of the Bx7OE subunit to the total amount of high-molecular-weight glutenin subunits among the 31 bread wheat varieties was 41.8%, which is much higher than that of varieties with the normal Bx7 subunit (generally at 30%). Flour quality analysis of seven representative varieties with Bx7OE and three with the normal Bx7 subunit showed that the varieties with Bx7OE generally displayed better gluten strength than those with the normal Bx7 subunit. STS markers demonstrated that, in addition to the 31 bread wheat varieties with Bx7OE, no PCR products were obtained from the related Triticum and Aegilops species. This suggests that the retroelement-mediated recombination event at the Glu-B1 locus could have occurred more recently, later than the formation of hexaploid wheat. The Bx7OE subunit is mainly distributed in some bread wheat varieties from American countries with a low frequency, which is of particular importance for the quality improvement of wheat gluten.